Brand management in top-tier college athletics: examining and explaining mark-usage policies. Issue 3 (1st August 2016) - Kellison, Timothy B.; Bass, Jordan R.; Oja, Brent D.; James, Jeffrey D.
Abstract : Purpose: – The practice of an interscholastic athletic department reproducing the logo of a collegiate team for its own use is becoming increasingly visible. In response to this growth, many collegiate licensing departments have begun actively enforcing zero-tolerance policies that prohibit third parties from using their respective colleges' trademarks. Conversely, other institutions have exercised discretion by allowing high school programs to use their athletic departments' logos only after receiving assurances from the high school that it will adhere to strict usage guidelines. The paper aims to discuss these issues. Design/methodology/approach: – The paper provides a thorough discussion on the concept of brand dilution and its application to sport. More specifically the study gives an account of the strategies employed by trademark specialists to protect (and in some cases, enhance) the equity of their brands. To identify these strategies, a qualitative questionnaire was employed, which was completed by 13 brand managers representing institutions from the Atlantic Coast Conference, Big 12 Conference, Big Ten Conference, Mid-American Conference, Missouri Valley Conference, Pac-12 Conference, and the Southeastern Conference. Findings: – Qualitative questionnaire responses from collegiate brand managers suggest that licensing departments differ in their perceptions of the outcomes associated with allowing logo replication in high school athletic departments. Originality/value: – Perceived consequences of two enforcement strategies – prohibitive and cooperative – are highlighted, as are implications and directions for future research.